1948
DOI: 10.1111/j.1096-3642.1948.tb00372.x
|View full text |Cite
|
Sign up to set email alerts
|

The Morphology of the Ethmoidal Region of Sphenodon and Lizards

Abstract: Summary. The nasal organs of Sphenodon and lizards are considerably modified by the mode of life, which in turn influences the form of the nasal capsule. The anterior chamber functions as a filter in preventing foreign bodies from entering the respiratory tract. It is well marked in terrestrial forms that are specialized for a deserticolous existence, but it is very reduced in arboreal forms. The lateral nasal gland passes its mucoid secretion into the anterior chamber, and serves to bind to the epithelium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
0
8

Year Published

1961
1961
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(87 citation statements)
references
References 30 publications
3
76
0
8
Order By: Relevance
“…This was generally found in lizards and snakes by Haller von Hallerstein (1934). The olfactory peduncle has been recorded by many authors in the majority of Sauria and serpents, and hence, it seems a common feature in squamates (Goldby, 1934;Pratt, 1948;Hegazy, 1969 Soliman (1964) found that the olfactory peduncles are absent and the olfactory bulbs sessile, i.e., join the cerebral hemispheres directly.…”
Section: Discussion:-mentioning
confidence: 99%
“…This was generally found in lizards and snakes by Haller von Hallerstein (1934). The olfactory peduncle has been recorded by many authors in the majority of Sauria and serpents, and hence, it seems a common feature in squamates (Goldby, 1934;Pratt, 1948;Hegazy, 1969 Soliman (1964) found that the olfactory peduncles are absent and the olfactory bulbs sessile, i.e., join the cerebral hemispheres directly.…”
Section: Discussion:-mentioning
confidence: 99%
“…A fenestra pode ser delimitada dorsalmente pelo processo alar superior, e ventralmente pelo processo alar inferior (Pratt, 1948).…”
Section: Cápsula Nasalunclassified
“…Esta abertura corresponde à passagem do ramo lateral etmóide do nervo oftálmico (Pratt, 1948). O nervo oftálmico é uma das ramificações do nervo trigêmeo (V) (Romer, 1956).…”
Section: Cápsula Nasalunclassified
See 2 more Smart Citations